Pakistan Army Green Book 2012 : National Security Issues - Pakistan Army; Editors : Brig. Khushnud Iqbal, Sl (M); Col. Wajid Qayum Paracha; Lt. Col. Saqib Jehangir Mirza (GHQ, Rawalpindi Pakistan Army, 2012)
Content of the book are the writer's personal views and are not to be taken as official opinion/policy.
Include Color Illustration
Keywords: Pakistan. Army -- Pakistan. -- Army -- Periodicals